Pertimbangan Hakim dalam Pemberian Izin Poligami akibat Perzinahan Suami yang Mengakibatkan Kehamilan: Studi di Pengadilan Agama Makassar - Ramadani, Rika; Hardiansyah, Lm Isman; Azisah, Nur (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
Applications for polygamy permits filed due to marital infidelity resulting in pregnancy present complex legal and moral dilemmas, as they bring together legal certainty, Sharia values, and the protection of children's rights. This article aims to analyze the judge's considerations in granting a polygamy permit in Decision Number 2310/Pdt.G/2020/PA.Mks at the Makassar Religious Court, by examining the extent to which the judge integrated the principles of Islamic law, positive law, and substantive justice. The main issue of this study focuses on the normative basis for granting permission for polygamy due to pregnancy outside of marriage and its implications for the consistent application of Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law. This research uses a qualitative method with a case study approach, through descriptive-analytical analysis of court decisions, legislation, and relevant Islamic legal literature. The results of the study show that pregnancy resulting from adultery is not explicitly regulated as a reason for polygamy in positive law, so judges tend to use the approach of maslahat and protection of children's rights as the main basis for consideration. However, this approach creates tension between the formal procedures of polygamy—such as the consent of the wife and economic capacity—and the risk of normalizing violations of marriage norms. The novelty of this research lies in revealing the pattern of judges' reasoning that places the interests of children as a substantive justification for granting permission for polygamy, even though it has the potential to obscure the function of polygamy as a conditional and limited legal institution. This research implies the need to formulate more explicit judicial guidelines so that considerations of child protection do not develop into legal legitimization of violations of moral norms and marriage laws.